2021
DOI: 10.1038/s41467-021-27156-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of disease-linked hyperactivating mutations in UBE3A through large-scale functional variant analysis

Abstract: The mechanisms that underlie the extensive phenotypic diversity in genetic disorders are poorly understood. Here, we develop a large-scale assay to characterize the functional valence (gain or loss-of-function) of missense variants identified in UBE3A, the gene whose loss-of-function causes the neurodevelopmental disorder Angelman syndrome. We identify numerous gain-of-function variants including a hyperactivating Q588E mutation that strikingly increases UBE3A activity above wild-type UBE3A levels. Mice carryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 80 publications
(143 reference statements)
3
21
0
Order By: Relevance
“…While Pro815 is near the known catalytic domain Cys820, evidence confirming that Pro815 itself resides within a functional domain has not been established; therefore, it is unclear if the criteria have been met for PM1 (Table 2). Finally, substitutions in the same location, Pro815His and Pro815Arg, have been functionally characterized and determined to lead to loss of function 15 (PM5_moderate). Additionally, since all the in silico tools predict a damaging effect on the protein, PP3_supporting applies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Pro815 is near the known catalytic domain Cys820, evidence confirming that Pro815 itself resides within a functional domain has not been established; therefore, it is unclear if the criteria have been met for PM1 (Table 2). Finally, substitutions in the same location, Pro815His and Pro815Arg, have been functionally characterized and determined to lead to loss of function 15 (PM5_moderate). Additionally, since all the in silico tools predict a damaging effect on the protein, PP3_supporting applies.…”
Section: Resultsmentioning
confidence: 99%
“…Different amino acid changes in nearby residues of Pro815 have been shown to have deleterious effects on nuclear localization, catalytic function, or protein folding 17 . Substitutions in the same location, Pro815His and Pro815Arg, have been reported and were determined to lead to loss of function 15 . Furthermore, it is evident from the three‐dimensional modeling of UBE3A variant p.(Pro815Ser) that the change of amino acid from Proline to Serine at position 815 causes a conformational change in the protein (Figure 1D–G).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the pleiotropic influence of Ube3a on multiple molecular and transcriptional pathways, ranging from protein degradation to transcriptional effects on multiple genes, our results cannot be unambiguously attributed to a specific function of Ube3a. Mechanistic inferences are further compounded by uncertainty regarding the ligase activity of the C-terminal flagged Ube3a copies overexpressed in our mouse model (Smith et al, 2011): whilst in vitro studies showed loss of ligase function upon C-terminal Ube3a tagging (Salvat et al, 2004;Kühnle et al, 2013;Avagliano Trezza et al, 2021;Bossuyt et al, 2021;Weston et al, 2021), in vivo investigations revealed largely increased ubiquitination levels in brain lysates from Ube3a2X mice (Khatri et al, 2018) and comparable behavioral phenotypes when C-or N-terminal tagged Ube3a is overexpressed in this model (Krishnan et al, 2017). Because Angelman syndrome (AS) reflects impaired Ube3a ligase function (Cooper et al, 2004), our finding that the transcriptional profile of Ube3a2X mice exhibits robust overlap with 15qdup, but not with AS, argues against a prominent loss of ligase activity in our model, and suggests that that the reported phenotypes may primarily reflect Ube3a-mediated transcriptional dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been developed and used to compare two protein structures to evaluate the accuracy of predicted models and predict the structural effects of mutations, all with advantages and limitations [ 64 , 65 , 66 , 67 ]. For instance, the root-mean-square deviation (RMSD) is one of the most commonly used methods for computing backbone alignment scores, but this distance-based method is size-dependent and has low confidence in certain circumstances [ 48 , 68 ].…”
Section: Discussionmentioning
confidence: 99%